Korelasi Skor Quizizz Mastery Peak dan Nilai Tes Tertulis Dalam Pemahaman Teks Analytical Exposition Siswa Kelas X SMA Negeri 1 Pekanbaru - Raihan Khairunisa; Finanta Okmayura; Molizarni Molizarni (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Technology is a part of human life. Technology contributes to the development of society and helps people's daily lives. Nowadays students spend more time with their cell phones. Learning media in the field of technology that can be used in the teaching and learning process is the quiz on the Quizizz 'Mastery Peak' application because it can replace the traditional method of using paper and pen. On the other hand, traditional learning methods in the form of written tests that still use paper and pen have positive effects, for example students can complete their work more efficiently. In the world of education, especially in English subjects, students study various genres of text, one of which is studying analytical exposition text in class X SMA Merdeka Curriculum. This study aims to determine whether or not there is a correlation between Quizizz 'Mastery Peak' scores and written test scores in understanding analytical exposition texts of grade X students of SMA Negeri 1 Pekanbaru. The sample in this study amounted to 40 people using purposive sampling technique. The method used in this research is quantitative correlation. Data analysis technique using correlation test obtained significance number of 0.535, where 0.535 > 0.05 then H0 is accepted Ha is rejected. This means that there is no correlation between Quizizz 'Mastery Peak' scores and students' written test scores in understanding analytical exposition text.